Case Report: Effective Use of the Orticochea Flap in the Surgical Treatment of Non-Hodgkin Lymphoma - Anastasia Dessy Harsono; Metaudina Chandra Pratiwi; Dominic Melino Tjokrovonco (The ASEAN Journal of Military and Preventive Medicine, 2024)
Non-Hodgkin lymphoma is a malignant disease arising from lymphoid tissues, primarily affecting the lymph nodes. The clinical manifestations and histological appearances of non-Hodgkin lymphoma are diverse, typically presenting with swelling, pain, and ulcers in the head and neck region. This case report discusses the management of a 55-year-old immunocompetent female patient presenting with a large, painless mass extending from the neck to the occipital region of the scalp, mimicking the features of a sarcoma. Closing scalp defects poses a significant challenge for plastic surgeons due to the limited tissue and variable elasticity of the scalp. Orticochea flap, also known as the "banana peel" flap was performed on the patient after the removal of the tumor mass. The orticochea flap technique allows for greater surface area coverage while maintaining vascularity, resulting in quicker procedures and good aesthetic outcomes.